On drawing a line through the spectrogram: how do we understand deficits of vocal pitch imitation? - Pfordresher, Peter Q.; Larrouy-Maestri, Pauline (Frontiers in Human Neuroscience, 2015)
In recent years there has been a remarkable increase in research focusing on deficits of pitch production in singing. A critical concern has been the identification of “poor pitch singers,” which we refer to more generally as individuals having a “vocal pitch imitation deficit.” The present paper includes a critical assessment of the assumption that vocal pitch imitation abilities can be treated as a dichotomy. Though this practice may be useful for data analysis and may be necessary within educational practice, we argue that this approach is complicated by a series of problems. Moreover, we argue that a more informative (and less problematic) approach comes from analyzing vocal pitch imitation abilities on a continuum, referred to as effect magnitude regression, and offer examples concerning how researchers may analyze data using this approach. We also argue that the understanding of this deficit may be better served by focusing on the effects of experimental manipulations on different individuals, rather than attempt to treat values of individual measures, and isolated tasks, as absolute measures of ability.